Epstein-Barr virus-associated lymphoproliferative disorder in colon with the development of hemophagocytic syndrome of an immunocompetent patient - Wang, Hai-Zhou; Gao, Chang; Zhou, Rui; Shi, Xian-Yan; Yu, Ming-Xia; Lin, Jun; Zhao, Qiu; Liu, Jing (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Wang HZ, Gao C, Zhou R, et al. Epstein-Barr virus-associated lymphoproliferative disorder in colon with the development of hemophagocytic syndrome of an immunocompetent patient. Turk J Gastroenterol 2019; 30(11): 995-6.